Out-of-pocket healthcare expenditures of Turkish households living with rare diseases - Koçkaya, Güvenç; Oguzhan, Gülpembe; Ökçün, Selin; Kurnaz, Mustafa (Frontiers in Public Health, 2023)
This study aims to determine the out-of-pocket health expenditures of households in Turkey where individuals with rare diseases are residing. The research population consisted registered members of associations who are members of the Rare Diseases Network. In addition to the general analysis including all participants, expenditures based on characteristics of disease holders were also calculated. A total of 439 participants were included in the analysis. We determined that special nutrition was the highest expenditure group and emergency departments were the lowest expenditure group. When all the participants were evaluated, the average cost of rare diseases was found to be ₺22,743 (€2,877). A significant relationship was found between income status and out-of-pocket health expenditures (p= 0.012). Policy makers should consider inclusion of special nutritional products and medical/non-medical devices used in treatment of rare diseases within the scope of reimbursement and the development of orphan drug legislation as the first actions to be taken.